ARA relief campaign in the Volga region, Jewish anthropometric statistics, and the scientific promise of integration. Issue 1 (24th May 2019) - Mogilner, Marina
Argument: The article builds a case for the Society for the Protection of the Health of the Jewish Population (Obshchestvo Okhranenia Zdorov'ia Evreiskogo Naselenia [OZE]) as a project of medicalized modernity, a mass politics of Jewish self-help that relied on a racialized and medicalized vision of a future Jewish nation. Officially registered in 1912 in St. Petersburg, it created the space for a Jewish politics that focused on the state of the collective Jewish body as a precondition for Jewish participation in any version of modernity. OZE futurism survived the years of World War I and the Russian Civil War, when the organization had to concentrate on rescue and relief rather than on facilitating the development of new bodies and souls. New archival evidence reveals how race science, medical statistics, and positive eugenics became composite elements of the Jewish anticolonial message and new subjectivity.